2005
DOI: 10.2220/biomedres.26.123
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor-induced hyperexcitability of rat sensory neuron in culture

Abstract: Abnormal spontaneous firing of primary sensory neurons is considered to be a cause of neuropathic pain. However, pathogenic mechanisms of hyperexcitable sensory neurons in neuropathic model animals are unclear. We examined effects of chronic treatment of nerve growth factor (NGF), one of candidate mediators for the pathogenesis, on excitability of sensory neurons by voltage-clamped recording in a cell-attached configuration. From rat dorsal root ganglion (DRG) neurons cultured without NGF, only stable holding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 34 publications
2
15
0
4
Order By: Relevance
“…Cell isolation and culture: DRG neurons were isolated from adult male Sprague-Dawley rats (7-12 weeks old), using procedures reported previously [21,23,30]. Rats were killed by cervical dislocation under diethyl ether inhalation anesthesia.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell isolation and culture: DRG neurons were isolated from adult male Sprague-Dawley rats (7-12 weeks old), using procedures reported previously [21,23,30]. Rats were killed by cervical dislocation under diethyl ether inhalation anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…Such action of NGF is not restricted to the peripheral tissues, but is also seen in the CNS [16,25]. Recently, we reported that rat DRG neurons cultured in the presence of NGF showed spontaneous action potentials [21] and spontaneous rises and falls in the intracellular Ca Among DRG neurons, A-and C-neurons are generally considered to be involved in nociception. It is widely accepted that NGF plays roles in cell survival, apoptosis, differentiation, the growth of axons/dendrites and the expression of various proteins through two types of receptors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Він через внутрішньоклітинні шляхи підсилює відповіді нейронів спінальних гангліїв на капсаїцин [16,17]. Культивуван-ня нейронів з надлишковою концентрацією ФРНТ (50 -100 нг/мл) спричинює зміни у електрофізіологічних параметрах нейронів, що формують С-та Аδ-волокна [18,19]. По-казано, що цей пептид підвищує збудливість і має вплив на адренергічну модуляцію імпульсної активності нейронів спінальних гангліїв [20].…”
Section: вступunclassified
“…Ця модель корисна для визначення повільних змін у клітинних та міжклітинних механізмах, вивчення впливу нейротропних факторів, які виконують нейротрофічну та нейропротекторну функції і, навпаки, відіграють ключову роль при невропатичних порушеннях [13,14]. Однак для з'ясування впливу згаданих агентів потрібно дослідити електрофізіологічні по-каз ники цих нейронів у первинній культу рі.…”
Section: вступunclassified